More than PHB – the PHAmily of Copolymers: Justifications for Broader Use and Summary of Biodegradation Facts on Polyhydroxyalkanoates (PHA) – A Review - M. Lackner; P. Costa; M. Koller; M. Zinn (Chemical and Biochemical Engineering Quarterly)
Globally, a significant portion of plastics are mismanaged, ultimately ending up in the environment. While reducing, reusing, and recycling plastics should be the preferred end-of-life scenarios, biodegradable plastics are compatible with all of these routes and represent a promising alternative. Polyhydroxyalkanoates (PHAs), a family of polyesters synthesized by various microorganisms, stand out in this regard. The most common type of PHA, poly(3-hydroxybutyrate) (PHB), is particularly relevant as it is both biobased and biodegradable. Additionally, there is substantial knowledge about this thermoplastic polyester, its applications, and its commercial availability. However, over 150 other PHA building blocks have been identified, with some having been tested and developed for various promising applications. Despite this, not all PHA copolymers have been fully evaluated for their biodegradability across diverse environmental conditions. Nevertheless, due to their biosynthesis in living microorganisms, a good degree of biodegradability is expected. Moreover, PHAs can also be chemically recycled into valuable chemicals, positioning them as the biobased polymer with the most versatile end-of-life options. This review summarizes the current state of knowledge on PHA copolymers, their cur rent end-of-life pathways, the most relevant biodegradability standards, and their degradability by depolymerase enzymes.